Ex vivo evaluation of coronal and apical microbial leakage of root canal - Filled with gutta-percha or Resilon/Epiphany root canal filling material - de Almeida-Gomes Fabio; Maniglia-Ferreira Claudio; de Morais Vitoriano Marcelo; Carvalho-Sousa Bruno; Guimaraes Nadine Luisa; dos Santos Roberto; Gurgel-Filho Eduardo; Rocha Marcia (Wolters Kluwer Medknow Publications, 2010)
Objective: This ex vivo study compared coronal and apical microleakage of root canals filled with Resilon/Epiphany (RE) or gutta-percha/Grossman sealer (GP), using either lateral condensation (LC) or System B (SB) technique. Materials and Methods: Specimens in eight experimental groups were obturated using the following materials and techniques: Groups 1 and 3 - GP and LC; groups 2 and 4 - GP and SB; groups 5 and 7 - RE and LC; groups 6 and 8 - RE and SB. Apical and coronal leakages were tested using bacterial methods. For coronal analysis, the number of days required for complete contamination of the root canals was recorded according to observation of the brain heart infusion broth turbidity for 15 weeks. For apical analysis, the teeth were cleaved and the leakage was measured at 30 days. Data were collected for each sample and analyzed statistically with the Chi-square and ANOVA tests. Results: Leakage was found in all groups. The difference between filling materials, obturation techniques, and median time of leakage was not statistically significant for coronal ( P=0.847) and apical ( P=0.5789) leakages. Conclusion: There were no differences between the different filling materials (gutta-percha/Grossman sealer and Resilon/Epiphany) and obturation techniques (lateral condensation and system B technique) in coronal or apical leakages.